Posterior Tibial Nerve Schwannoma in the Popliteal Fossa: A Case Report - Lopez-Gonzalez, Luis; Pecos-Martin, Daniel; Gomez-Gonzalez, Mª Teresa; Fernandez-Carnero, Samuel; Gallego-Izquierdo, Tomas (Archives of Clinical and Medical Case Reports, 2020)
Schwannomas are uncommon disorders of peripheral nerves sheaths, presenting with particular neuropathic manifestations that are often misdiagnosed or undiagnosed. We offer a case report of a 36-year-old patient with an untypical schwannoma in the tibial nerve, causing long-lasting and increasingly exacerbated pain, misdiagnosed as a meniscus tear. The worsening symptoms, including hyperalgesia, allodynia and hypersensitivity, raised suspicion of malignancy. The patient underwent an ultrasound examination, where a compressive neuropathy was suspected. Finally, the presence of a large benign schwannoma was confirmed by magnetic resonance imaging. The tumour mass was excised and this gave way to a total and rapid relief of symptoms.